(untitled) (INCH : Journal of Infant and Child Healthcare, 2023)
Anemia is a condition where the level of red blood cells or hemoglobin (Hb) is lower than normal due to iron deficiency. The indicator of anemia in adolescent aged 15-17 years is<12.0g/dl. Adolescent girl are more susceptible to anemia compared to children and adults because they are in a growing phase that requires higher levels of nutrient, including iron. The aim of this study was to determine the factors associated with the occurrence of anemia in 85 adolescent girls at SMK Negeri 1 Rengat in 2020. The method used was an analtytical method with a cross-sectional The result obtained from the calculation of the Chi-square statistical test yielded a p-valueof 0.313. therefore, it can be concluded that there is no significant relationship between the factors associated with the occurrence of anemia in adolescent girls at SMK Negeri 1 in 2022